2004
DOI: 10.1207/s1532480xads0803_4
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Terrorism: Age and Gender Differences in Effortful and Involuntary Responses to September 11th

Abstract: (Connor-Smith, Compas, Wadsworth, Thomsen, & Saltzman, 2000) to examine coping and involuntary stress responses in reference to terrorism and across a wide age range was examined. Implications for coping theory and empirical research are explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 54 publications
2
41
0
3
Order By: Relevance
“…As we expected, women in this sample were more likely to express emotion in response to the September 11 th attacks, which is consistent with previous research that women use more emotion-focused coping than men (Diener, Sandvik, & Larsen, 1985;Ptacek, Smith & Dodge, 1994;Tamres, Janicki, & Helgeson, 2002;Wadsworth et al, 2004;Walker & Chestnut, 2003). As predicted, women were more likely to express sadness and less likely to express anger than men.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As we expected, women in this sample were more likely to express emotion in response to the September 11 th attacks, which is consistent with previous research that women use more emotion-focused coping than men (Diener, Sandvik, & Larsen, 1985;Ptacek, Smith & Dodge, 1994;Tamres, Janicki, & Helgeson, 2002;Wadsworth et al, 2004;Walker & Chestnut, 2003). As predicted, women were more likely to express sadness and less likely to express anger than men.…”
Section: Discussionsupporting
confidence: 91%
“…writing, therapy), women also sought more social activities (e.g., talking to people, attending church) than men (Wadsworth et al, 2004). Generally, men employ more problem-solving and avoidant-focused coping in stressful situations than women (Tamres, Janicki, & Helgeson, 2002).…”
Section: Gender Differences In Response To Traumatic Eventsmentioning
confidence: 99%
“…Due to the post-traumatic development found among paramedics with high level of selfefficacy, who used substances in order to overcome a stressful situation, it may be observed that the search for an alternative source providing stabilization may externalize as a change and a development in mental or spiritual area. Similarly, Wadsworth et al (2004) claim that there is often a shift (in connection with PTG of an individual) from simple behavioral coping strategies to strategies focused on internal survival.…”
Section: Specific Self-efficacy As Moderator Of the Relations Betweenmentioning
confidence: 99%
“…Research has demonstrated the importance of emotion-and problem-focused coping strategies in psychological resilience (Compas & Epping, 1993), and that people respond to stress through primary control efforts to problem solve, secondary control efforts to cognitively adapt to stress, or by disengaging from coping through denial (Wadsworth et al, 2004). Focusing on greening in post-disaster settings such as the aftermath of hurricanes, Okvat and Zautra (2014) argue that positive emotions are particularly important in resilience.…”
Section: Resiliencementioning
confidence: 99%